A Qualitative Analysis of Adolescent Responses to YouTube Videos Portraying Sexual and Gender Minority Experiences: Belonging, Community, and Information Seeking - Levinson, Jordan A.; Greenfield, Patricia M.; Signorelli, Jenna C. (Frontiers in Human Dynamics, 2020)
Sexual and gender minority youth are at risk for negative mental health outcomes, such as depression and suicide, due to stigma. Fortunately, sense of community, connection, and social support can ameliorate these deleterious effects. Youth express that most of their social support comes from peers and in-school organizations, but these sources require in-person interaction. Past research has identified social media sites as virtual and anonymous sources of support for these youth, but the role of YouTube specifically in this process has not been thoroughly explored. This study explores YouTube as a possible virtual source of support for sexual and gender minority youth by examining the ecological comments left on YouTube videos. A qualitative thematic analysis of YouTube comments resulted in six common themes in self-identified adolescents’ YouTube comments: sharing, relating, information seeking, gratitude, realization, and validation. Most commonly, adolescents shared feelings and experiences related to their identity, especially when they could relate to the experiences discussed in the videos. These young people also used their comments to ask for identity-related advice or information, treating the platform as a source of education. Results suggest that sexual minority youth’s use of YouTube is advantageous for social support and community, identity-related information, identity development, and overall well-being.